Tools for controlling a major global food and feed safety risk: Non-biological post-harvest procedures to decontaminate mycotoxins in food and feeds - Temba, Benigni A.; Sultanbawa, Y.; Kriticos, D.J.; Fox, Glen P.; Harvey, Jagger J.W.; Fletcher, M.T. (American Chemical Society, 2016)
Mycotoxin contamination of foods and animal feeds is a worldwide problem for human and animal health. Controlling mycotoxin contamination has drawn the attention of scientists and other food and feed stakeholders all over the world. Despite best efforts targeting field and storage preventive measures, environmental conditions can still lead to mycotoxin contamination. This raises a need for developing decontamination methods to inactivate or remove the toxins from contaminated products. At present, decontamination methods applied include an array of both biological and nonbiological methods. The targeted use of nonbiological methods spans from the latter half of last century, when ammoniation and ozonation were first used to inactivate mycotoxins in animal feeds, to the novel techniques being developed today such as photosensitization. Effectiveness and drawbacks of different nonbiological methods have been reported in the literature, and this review examines the utility of these methods in addressing food safety. Particular consideration is given to the application of such methods in the developing world, where mycotoxin contamination is a serious food safety issue in staple crops such as maize and rice.